Stakeholder perspectives on the management and impacts of whale-shark watching in Oslob, Cebu - OSENA, Krystyna (KDI School, 2016)
Recently, there has been a rise of the whale-shark watching industry in the Philippines, which has received both local and international attention for offering interaction activities. In order to analyze the sustainability of whale-shark watching in the country, Oslob, Cebu was chosen as the main case for the study. The researcher aimed to identify the present gains and/or losses in the socio-economic living conditions, analyze the present and potential threats to the current whale-watching and/or ecotourism activities conducted by the fishermen in Oslob, Cebu, and suggest policy changes and stakeholder efforts which are required to ensure the ecological and socio-economic sustainability of whale-shark watching activities in Oslob, Cebu. Through the development and utilization of a sustainability report card and direct observation of the whale-shark watching activities, the researcher was able to realize that the ecotourism activities produced numerous socio-economic benefits for the community. Nonetheless, the research findings also brought into light issues of lax management and implementation of regulations for the protection of whale-sharks. Hence, there is a need to reevaluate the implementation and monitoring of whale-shark watching in the area to ensure the sustainability of the whale-shark watching activities.
Thesis(Master) --KDI School:Master of Development Policy,2016